Research on Remaining Oil Characterization in Superheavy Oil Reservoir by Microgravity Exploration. (18th July 2022) - Lv, Qijun; Zheng, Aiping; Liang, Xiangjin; Chen, Hongfei; Ju, Shichang; Meng, Yanchong; Zhang, Hongyuan; He, Guolin; Deng, Shenshen; Li, Junfang
Abstract : Some physical processes such as oil and gas development, metal deposit collection, and groundwater resource migration can cause density changes, for which microgravity monitoring is the most intuitive method to monitor the density change process. Based on the basic principle of microgravity measurement and the idea of multiscale separation, a multiscale, second-order, surface-fitting, residual gravity anomaly extraction method is proposed to separate superimposed microgravity fields. In this method, regional fields of different scales are fitted and calculated successively with the measurement points as the center, so as to separate the gravity anomalies produced by different-depth density bodies. Results from actual data show that this method extracts the reservoir's residual density characteristics of plane gravity anomaly on the basis of remaining oil distribution characteristics, consistent with reservoir numerical simulation results. A three-dimensional least-squares inversion of the method for extracting residual gravity anomaly was carried out, with the inversion results consistent with the results of vertical remaining oil distribution characteristics and well-test production results.